National strategy for integrating palliative care into standard cardiac care for people living with heart failure: a position statement from the joint working group of the Swiss Societies of Cardiology and Palliative Care - Sobanski, Piotr Z.; De Perna, Maria Luisa; Eckstein, Sandra; Fusi-Schmidhauser, Tanja; Gaertner, Jan; Gonzalez-Jaramillo, Valentina; Hentsch, Lisa; Hertler, Caroline; Hullin, Roger; Hunziker, Lukas; Larkin, Philip; Mercoli, Jean-Baptiste; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHeart failure (HF) causes high symptom burden and shortens life expectancy. Implementation of Palliative Care (PC) concurrently with cardiologic guidelines-directed medical therapy (GDMT) improves quality-of-life (QoL) more than disease-oriented management alone but is underused. To facilitate provision of PC for people living with HF, the Swiss Society of Cardiology (SSC) and the Swiss Society for Palliative Care (palliative.ch) have created joint working-group.MethodsDyads representing cardiology and PC from Swiss HF centres have been identified. Through online voting, workshops and Delphi process priority topics for incorporation of PC into standard care for people with HF have been identified.Results18 experts, from 8 Swiss HF-centres identified main topics relevant for implementation of PC in usual HF care: timely recognition of unaddressed health-related needs of affected people and their relatives (using validated assessment tools ID-PALL or NAT-PD:CH at least as the triggers evolve), identifying key palliative interventions for care of people living with HF, identifying strategies to facilitate cooperation between specialist PC and cardiology, defining research agenda to investigate efficacy of PC interventions, quality of care criteria, and outcomes of PC provision in Switzerland.DiscussionImprovement of QoL of people with HF and their relatives could be greater if PC would be integrated in usual care timely. Frequent needs assessment, using validated tools helps to recognize people having unaddressed needs, and helps to replace the outdated, based on risk of dying, involvement of PC. Dialogue between both disciplines is crucial to provide care prolonging life of best quality during the whole journey living with disease.